Pengelolaan Hutan Kopi dan Aren dalam Inovasi Produk Kopi Aren Rasa Wine Non Alkohol di Kecamatan Kutalimbaru, Deli Serdang - Faisal Mirza, Deni; Guci, Dede Ansyari; Hasmidiarty, Hasmidiarty; Azahari, Delima Hasri (IPM2KPE, 2024)
This study aims to create an innovation in coffee-based culinary products by combining two plant materials, namely coffee and sap, to produce non-alcoholic grape-flavored sap coffee that has never been produced before. The method used in this study is descriptive qualitative with data collection techniques through FGD (Focus Group Discussion) with relevant stakeholders. The results of the study indicate that the coffee and sugar palm forests in the area are very productive and have great potential to support improving the welfare of farmers. In addition, the marketing model for this innovative sap coffee product is carried out offline and online, expanding the market reach. In conclusion, the innovation of non-alcoholic grape-flavored sap coffee can have a positive impact on improving the economy of coffee and sugar palm farmers in Sukamakmur Village, as well as opening up new job opportunities through productive management of natural resources. Keywords: Coffee Forest, Coffee Cultivation, Palm Coffee, Micro Business